PRAKTIK PERENCANAAN KEUANGAN: STUDI EMPIRIS TENTANG SIKAP DAN PERILAKU KEUANGAN RUMAH TANGGA DESA - Pangeran, Perminas (Faculty of Economics Universitas Atma Jaya Yogyakarta, 2013)
This study examines the attitudes and behaviors of the rural households toward personal nancial planningpractices, which encompases money management, insurance planning, investment planning, retirementplanning, and estate planning. The personal nancial planning is associated with demogra c, human capital,dan economic capital characteristics. This study is conducted via questionnaire survey. A survey data isobtained from 261 rural households by using set of structured quesionnaire. The results show a number ofinteresting ndings. First, the economic capitals are the important factors in in uencing attitudes and behaviorstoward household nancial planning. Second, the human capital, i.e. education of respondent is also in uenceattitudes and behaviors toward household nancial planning. Lastly, the demographic characteristics ofrespondent are not in uence attitudes and behaviors toward household nancial planning.Keywords: household nance, money, insurance, investment, retirement, estate